Heart failure risk estimation based on novel biomarkers. (3rd July 2021) - Ataklte, Feven; Vasan, Ramachandran S.
ABSTRACT: Introduction : Despite advances in medical care, heart failure (HF)-associated morbidity and mortality remains high. Consequently, there is increased effort to find better ways for predicting, screening, and prognosticating HF in order to facilitate effective primary and secondary prevention. Areas covered : In this review, we describe the various biomarkers associated with different etiologic pathways implicated in HF, and discuss their roles in screening, diagnosing, prognosticating and predicting HF. We explore the emerging role of multi-omic approaches. We performed electronic searches in databases (PubMed and Google Scholar) through December 2020, using the following key terms: biomarker, novel, heart failure, risk, prediction, and estimation. Circulating BNP and troponin concentrations have been established in clinical care as key biomarkers for diagnosing and prognosticating HF. Emerging biomarkers (such as galectin-3 and ST-2) have gained further recognition for use in evaluating prognosis of HF patients. Promising biomarkers that are yet to be part of clinical recommendations include biomarkers of cardiorenal disease. Expert opinion : Increasing recognition of the complex and interdependent nature of pathophysiological pathways of HF has led to the application of multi-marker approaches including multi-omic high throughput assays. These newer approaches have the potential for new therapeutic discoveries and improving precision medicine in HF.